Caracterização da força, da mobilidade, do desempenho funcional do membro superior e do perfil de risco de dor no ombro em atletas de esportes overhead - Secchi, Leonardo Luiz Barretti (Universidade Federal de São Carlos, 2023)
Introduction: Overhead athletes commonly experience shoulder pain, which is a major concern among basketball, handball, volleyball, and tennis for high performance teams. While some existing models of shoulder pain in these athletes are based on linear analyses and focus on the relationship between shoulder performance and shoulder pain, or seek to explain the underlying causes of shoulder pain, these models are limited by their failure to account for the complex interplay between shoulder and kinetic chain factors. Furthermore, the relationship between shoulder musculoskeletal parameters and kinetic chain performance in functional testing and risk profile for the development of shoulder pain in overhead athletes is unclear. Study 1. Objective: To verify the association of the isometric strength of the shoulder external rotators (ER) and serratus anterior (SA) with the performance of functional tests by Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST), Seat Medicine Ball Throw – (SMB-T) e Upper Seat Shot Put Test (USSP-T) in overhead athletes. Design: Cross-sectional study. Participants: Eighty overhead athletes with no history of surgery in the upper and lower limbs and trunk in the past year, and no painful symptoms in the upper body during the physical assessment were included. Main Outcome Measures: Preseason assessment included isometric strength of shoulder ER and SA, and perfomance of the CKCUEST, SMB-T, and USSP-T. Multiple linear regression analysis was performed to identify if the isometric strength of the shoulder ER and SA could explain the performance during the tests after controlling for sex. Results: The isometric strength of SA was associated (p<0.05) with the SMB-T and USSP-T with 4% of explain. The isometric strength of the SA was not associated (p>0.05) with the CKCUEST. The isometric strength of the ER was not associated (p>0.05) with any of the tests. Conclusion: The isometric strength of the SA predicted the SMB-T and USSP-T performance. Isometric strength of SA and shoulder ER was not associated with CKCUEST results in athletes overhead. Study 2. Objective: To investigate the association of interactions among variables of the shoulder, trunk, and hip with the shoulder pain occurrence in overhead athletes. Design: 6-month prospective cohort study. Main Outcome Measures: Preaseason assessment including shoulder external rotators (ER), serratus anterior (SA) and lower trapezius (LT) isometric strength, Hip Stability Isometric Test (HipSIT), Shoulder Internal Rotation (IR) Range of Motion (ROM), Low Flexion Test, Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST), Seat Medicine Ball – Throw (SMB-T), Upper Seat Shot Put – Test (USSP-T), Upper Quarter Y Balance Test (UQYBT), and Leg Lateral Reach Test (LLRT) using Classification and Regression Tree (CART) analysis. Participants: Ninety-five overhead athletes, with no history of surgery in the upper and lower limbs and trunk in the past year, and no painful symptoms in the upper body during the physical assessment were included. Results: Interactions among UQYBT, shoulder ER isometric strength, and USSP-T were identified in overhead athletes. CART analysis indicated the interaction by UQYBT score ≤ 88.5%, and shoulder ER isometric strength ≥ 0.780 N/kg in athletes without shoulder pain (RR: 0.02, 95%CI (0.00, 0.44)) p<0.05, and UQYBT score above ≥ 88.5% and USSP-T performance ≥ 3.175m were identified with shoulder pain (RR: 14.09, 95%CI (3.27 – 60.56)) p<0.05. The model correctly classified 77.4% of athletes without shoulder pain and 100.0% of athletes with shoulder pain. The area under the ROC curve was 0.89 (95%CI: 0.83, 0.96; p< 0.001). Conclusion: The shoulder pain occurrence in overhead athletes was associated with interactions among UQYBT, shoulder ER isometric strength, and USSP-T.
Characterization of strength, mobility, functional performance of the upper limb, and risk profile of shoulder pain in overhead athletes
Keywords: Arremesso; Avaliação funcional; Análise não-linear; Esporte; Throw; Functional assessment; Non-linear analysis; Sport; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL